MOSLEM SCHOLARS’ VIEW ON THE POSITION OF ARABIC WITHIN THE CLASSIFICATIONS OF SCIENCES - Laila, St. Noer Farida (Jurnal Bahasa Lingua Scientia, 2011)
Systematic studies on Arabic language had taken place since the early classical age of Islam. Therefore, Arabic language and all its aspects became the first science developed by Moslem scholars. However, the scholars always sought to subordinate the study of Arabic philology and grammar and to limit the influence of grammarians over young men.  And it is a fact that the scholars differed in viewing whether the Arabic is the subordinate to religious sciences or to foreign sciences. From the different argument put forward by the scholars, it is clear that their debates were closely related to the dichotomy of sciences that developed since the third/ ninth century.